2006
DOI: 10.1248/yakushi.kj00004483559
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Disposition of Silodosin (KMD-3213)

Abstract: After a single oral dose of silodosin in male rats , male dogs and healthy human male volunteers , Cmax occurred with − in about 2 h , indicating rapid absorption . The elimination half − 1ife was about 2 h in rat and dog, but 4. 7 h (fasted)and 6. Oh (non − fasted)in humans . Absolute bioavailability values in rat , dog and human were about 9 , 25 and 32 % , respec − tive 且 y , In rat and dog , total blood clearance was almost equivalent to the hepatic blood flow , but that in human was low (20 %), demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This is consistent with previous results indicating that silodosin was mainly metabolized in the liver and excreted through the feces after oral administration. 13) In summary, silodosin is safe and well tolerated in healthy Chinese subjects following single-dosing escalation once daily in the dose range of 2-12 mg, and multiple-dosing twice daily (4 mg per administration). Mild adverse events like headache, dizziness, and TBIL elevation are frequently encountered and are related to dose escalation but reversible after drug discontinuation.…”
Section: )mentioning
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous results indicating that silodosin was mainly metabolized in the liver and excreted through the feces after oral administration. 13) In summary, silodosin is safe and well tolerated in healthy Chinese subjects following single-dosing escalation once daily in the dose range of 2-12 mg, and multiple-dosing twice daily (4 mg per administration). Mild adverse events like headache, dizziness, and TBIL elevation are frequently encountered and are related to dose escalation but reversible after drug discontinuation.…”
Section: )mentioning
confidence: 91%
“…Results from a study in rats revealed that silodosin underwent biliary excretion and enterohepatic circulation, 13) and these phenomena may cause the re-absorption of silodosin in the intestinal tract. A possible reason could be the powders of silodosin are distributed to different sites after disintegration of the capsules in the gastrointestinal tract, thereby resulting in the delay of absorption and the dual-peaks of absorption.…”
Section: )mentioning
confidence: 99%
“…Accordingly, the reversal of multidrug resistance of microorganisms by inhibiting their ABC transporters is a promising avenue to overcome infectious diseases. [137] N N N O Cl Cl alpidem (hypnotic) [262] S N N thioflavin T (dye) [263] N N aprindine (antiarrhythmic) [264] N N imipramine (antipsychotic) [ [141] NH N N auramine O (dye) [194] NH 2 H 2 N NH 2 pararosaniline (dye) [267] Overlapping Ligand Specificity of P-Glycoprotein [271] O H N OH alprenolol ( -blocker) [175] N N N binedaline (antipsychotic) [162] N N N F OH F 3 C tefludazine (antipsychotic) [102] O H N OH bornaprolol ( -blocker) [43] O H N OH alprenolol ( -blocker) [175] ( [280] N N Cl medazepam (benzodiazepine) [226] [283] O N N COOH rhodamine B [119] Ferenc Zsila ( O N H OH penbutolol ( -blocker) [284] O N H OH propranolol ( -blocker) [177] O O OH phenprocoumon (anticoagulant) [256] O O O OH warfarin (anticoagulant) [137] N NH pipequaline (antipsychotic) [162] S N N N perazine (antipsychotic) [102] [90] S O N H OH tertatolol ( -blocker) [43] O N H OH propranolol ( -blocker) [177] S N N N S thiethylperazine (antiemetic) [291] S N N N Cl prochlorperazine (antipsychotic) [214] S S N HOOC tiagabine (antiepileptic) [292] S S N tipepidine (antitussive) [102] N N OH tolterodine (antimuscarine) [296] N N Cl chlorpheniramine (antihistamine) [43] HN acriflavine (dye) [301] N N N acridine orange (dye) [51] Overlapping Ligand Specificity of P-Glycoprotein N N D-3...…”
Section: Comparison Of Ligand Binding Specificities Of P-gp and Non-mmentioning
confidence: 99%
“…Identification of reactive or toxic metabolites is essential to avoid the toxicity and helps to modify the structure by means of synthetic chemical transformations . Some methods have been reported for the determination of SLD in biological fluids …”
Section: Introductionmentioning
confidence: 99%